IFPA Meeting 2010 Workshop Report I: Immunology; Ion transport; Epigenetics; Vascular reactivity; Epitheliochorial placentation; Proteomics - Abad, C.; Antczak, D. F.; Carvalho, J.; Chamley, L. W.; Chen, Q.; Daher, S.; Damiano, A. E.; Dantzer, V.; Diaz, P.; Dunk, C. E.; Daly, E.; Escudero, C.; et al. (W B Saunders Co Ltd, 2011)
Workshops are an important part of the IFPA annual meeting. At IFPA Meeting 2010 there were twelve themed workshops, six of which are summarized in this report 1. The immunology workshop focused on normal and pathological functions of the maternal immune system in pregnancy. 2. The transport workshop dealt with regulation of ion and water transport across the syncytiotrophoblast of human placenta. 3. The epigenetics workshop covered DNA methylation and its potential role in regulating gene expression in placental development and disease. 4. The vascular reactivity workshop concentrated on methodological approaches used to study placental vascular function. 5. The workshop on epitheliochorial placentation covered current advances from in vivo and in vitro studies of different domestic species. 6. The proteomics workshop focused on a variety of techniques and procedures necessary for proteomic analysis and how they may be implemented for placental research. (C) 2011 Published by IFPA and Elsevier Ltd.
Keywords: Placenta; Trophoblast; Workshops